Canada : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2003 Article IV Consultation highlights that Canada's strong policy framework has brought impressive economic results, and the Canadian economy has proven exceptionally resilient in the face of the recent global downturn. Economic activity slowed relatively modestly in 2001, with only one quarter of output decline recorded, and growth recovered strongly thereafter, averaging 4 percent over the subsequent four quarters. Household consumption and residential investment have remained robust. Household and business demand was supported by sustained productivity growth, rapid growth of employment and labor incomes, and gains in real estate prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet